Antibacterial Activity of Endophytic Fungi Isolated from Parang Romang (Boehmeria virgata (G.Forst) Guill) Leaves Against Gastrointestinal Pathogens - Rusli, Rusli; Nurung, Ayyub Harly; Sandyna, Muh. Ivan (Fakultas Farmasi, Universitas Muslim Indonesia, 2024)
Parang romang (Boehmeria virgata (G.Forst) Guill) is a plant traditionally used for treating various digestive tract infections. However, obtaining bioactive compounds directly from the plant requires significant biomass. Therefore, endophytic fungi, sourced from specific plant parts, are explored for their ability to produce similar bioactive compounds. The research examined the potential antibacterial activity of endophytic fungi isolated from parang romang leaves against common gastrointestinal pathogens. The methods used in was, characterization of endophytic fungal isolates, and antagonistic activity was evaluated using the agar diffusion method. The results showed that the endophytic fungal strains, namely isolates IFBV 6, IFBV 7, and IFBV 10 could inhibit the bacteria Escherichia coli, Salmonella typhi, Shigella dysenteriae, and Vibrio cholera. With an average zone of inhibition for each strains isolate against Esherichia coli respectively 11.53 mm, 10.49 mm, and 14.85 mm; Salmonella typhi 14.47 mm, 8.66 mm, and 15.51 mm; Shigella dysenteriae 22.28 mm, 13.76 mm, and 15.33 mm; and Vibrio cholera 16.91mm, 11.94mm, 15.16mm. In conclusion, isolated endophytic fungal strains hold promise as potential as antibacterialn agents.